EFEKTIFITAS METODE DEMONSTRASI DAN PRAKTIKUM DALAM PEMBELAJARAN DI SD NEGERI LOSARI PLOSO - Siti Wulandari Novitasari; M. Qoyum Zuhriawan; M. Aliyul Wafa (PT. Hasba Edukasi Mandiri, 2025)
Success in learning is an achievement obtained by students through the learning process in the form of abilities, attitudes and skills. The learning outcomes in this study are the results of learning to perform ablution. The purpose of the study was to determine the effect of using demonstration and practicum methods on improving student learning outcomes in Islamic Religious Education subjects at SD Negeri Losari Ploso Jombang, East Java in the 2024/2025 Academic Year. This type of research uses a quasi-experimental method. The sample in the study was 32 students in class IV A as the experimental class who were given treatment using the Practicum method, and also 30 students in class IV B as the control class who were given treatment using the Demonstration method. The sampling technique was Purposive Sampling which was chosen based on teacher considerations, the instrument in this study was a multiple-choice test. The data collection technique was in the form of a test (Pretest-Posttest) totaling 25 questions, observation, interviews and tests. While the data analysis technique used in the study was the independent sample t-test with the SPSS application. The application of the demonstration method given treatment to the control class can significantly affect student learning outcomes in fiqh material. Then in the experimental class given treatment with the practicum method can affect student learning outcomes. Based on the average value of student learning outcomes before treatment on the results (Pre-test) with the learning outcomes obtained in the experimental class based on an average value of 66.63, then on the learning outcomes of the control class with an average value of 66.31. After both classes were given treatment in the experimental class using the practicum method while in the control class using the demonstration method, it can be seen that the average value of student learning outcomes after being given treatment on the results (Post-test) of the experimental class was 82.33 and the control class was 74.53.Thus, it can be said that there is a significant influence on the use of demonstration and practicum methods on student learning outcomes in Islamic Religious Education subjects at Losari Ploso Elementary School, Jombang, East Java in the 2024/2025 Academic Year.